The Prognostic Utility of the Triceps Skinfold Thickness Albumin Index in Colorectal Cancer Patients with Cachexia - Liu, Xiao-Yue; Lin, Shi-Qi; Ruan, Guo-Tian; Zheng, Xin; Chen, Yue; Zhang, He-yang; Liu, Tong; Xie, Hai-Lun; Shi, Han-Ping (Nutrition and cancer, 2025)
To develop a simple and convenient inflammation-nutrition-adiposity biomarker to complement the TNM staging system, further assess the prognosis of patients with colorectal cancer cachexia. This study was a multi-centre cohort study. The triceps skinfold thickness-albumin index (TA) was calculated by combining the triceps skinfold thickness (TSF) and serum albumin levels. Kaplan-Meier analysis and Cox proportional risk regression models were used to assess the relationship between the TA and all-cause mortality. Internal validation was carried out. We included 1025 patients with colorectal cancer cachexia, 61.2% of whom were male, with a mean age of 58.91 (12.45) years. As the TA increased, overall mortality decreased in female patients (hazard ratio [HR], 0.95) but not in male patients (HR, 0.99). Multivariate Cox analysis showed that patients in the normal TA group had a significantly lower risk of death than those in the low TA group (HR, 0.53, 95% CI, 0.40-0.72). Patients with a normal TA had a lower risk of malnutrition, poor quality of life, and poor short-term prognosis than those with a low TA. TA index enables clinicians to assess the prognosis of patients as early as possible to improve the survival of patients with colorectal cancer cachexia.